2015
DOI: 10.1177/1354067x15570488
|View full text |Cite
|
Sign up to set email alerts
|

Parent–teacher meetings as a unit of analysis for parent–teacher interactions

Abstract: The attempt to establish the decisive factors in psychological research, from an idiographic perspective, firstly involves examining the meanings entailed in this epistemological paradigm. Specifically, our work sets out to assess the possibilities of using this perspective with reference to parent-teacher relationships, as expressed through parent-teacher meetings. Said meetings present their own specific features which distinguish them from all the other kinds of meetings examined in literature (clinical, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Every school sets guidelines, but carrying out disciplinary interventions is the responsibility of the single teacher and is part of a teacher's professional role. If the need for disciplinary interventions persists on the pupil's part, Italian Educational Law has established the obligation of organizing periodical parent-teacher meetings for the purpose of discussing children's scholastic improvement on a regular basis, and to inform parents of any difficulties that may have been encountered recently, with regard to scholastic performance and the quality of pupils' relationships with teachers and peers (Gastaldi, Longobardi, Quaglia, & Settanni, 2015). The necessity for constant close cooperation between families and schools is enshrined by Article 29/2 of the Contratto Collettivo Nazionale del Lavoro (2006Lavoro ( /2009, which states, "Individual obligations include such activities as: ( .…”
Section: Discussionmentioning
confidence: 99%
“…Every school sets guidelines, but carrying out disciplinary interventions is the responsibility of the single teacher and is part of a teacher's professional role. If the need for disciplinary interventions persists on the pupil's part, Italian Educational Law has established the obligation of organizing periodical parent-teacher meetings for the purpose of discussing children's scholastic improvement on a regular basis, and to inform parents of any difficulties that may have been encountered recently, with regard to scholastic performance and the quality of pupils' relationships with teachers and peers (Gastaldi, Longobardi, Quaglia, & Settanni, 2015). The necessity for constant close cooperation between families and schools is enshrined by Article 29/2 of the Contratto Collettivo Nazionale del Lavoro (2006Lavoro ( /2009, which states, "Individual obligations include such activities as: ( .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the teacher plays an important role in mediating relationships between classmates, helping them in managing conflicts within the class group, encouraging correct behaviours, and discouraging incorrect behaviours (Gastaldi, Longobardi, Quaglia, & Settanni, 2015; Quaglia, Gastaldi, Prino, Pasta, & Longobardi, 2013). Consequently, a positive student–teacher relationship can decrease the frequency of aggressive behaviours (Jungert, Piroddi, & Thornberg, 2016; Longobardi, Badenes‐Ribera, et al ., 2018; Longobardi, Iotti, et al ., 2018; Longobardi, Prino, Fabris, & Settanni, 2017; Marengo et al ., 2018) and eventually promote prosocial behaviours, which contributes more generally to a greater sense of inclusion and a positive relational climate in the classroom (Hamre & Pianta, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating the role of STRs in promoting students' well-being and academic achievement in the perspective of attachment theory, have shown that teachers which act as a “secure base”—that is, being available, responsive and accepting of students' needs—improve their students' commitment (Hughes et al, 2008; Myers and Pianta, 2008; Gastaldi et al, 2015), competence (Baker, 2006), and favor the development of their learning interests (Hughes et al, 2008; Quaglia et al, 2013). Low-conflict relationships with teachers favor an increase in positive classroom climate and students' perceived teacher support, and a decrease in students' negative experiences (Hamre et al, 2008; O'Connor, 2010).…”
Section: Introductionmentioning
confidence: 99%